Two new Trachyphloeini (Coleoptera; Curculionidae; Entiminae) from Laos - Borovec, Roman; Anderson, Robert (Zootaxa, 2024)
Two new species of the tribe Trachyphloeini from Laos, Laohajekia uniformis Borovec and Anderson sp. nov. and Trachyphloeosoma newthayorum Borovec and Anderson sp. nov., are described, illustrated and compared with related species. Trachyphloeosoma roelofsi (Sharp) is recorded from Laos for the first time.